Employment Expectations and Labour Force Participation in Canada - Donner, Arthur; Lazar, Fred (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1974)
This paper incorporates a role for expectations in the short-run behavior of labour supply decision, presents a theory introducing labour market expectations as a variable influencing labour supply, and discusses the relative merits of the expectations model vis-à-vis the traditional model using the empirical results derived in this work.